Adsorption behaviors of SF6 decomposition gas on Ni-doped ZIF-8:A first-principles study. (May 2021) - Li, Song; Wei, Xiao; Zhu, Shiping; Zhou, Qu; Gui, Yingang
Abstract: The detection of toxic gas decomposition in gas insulated switchgear is an important technology to predict and judge equipment failure. In this paper, the adsorption model is established by the first principles. It is found that the band gap of Ni-doped ZIF-8 clusters is reduced and the selectivity is enhanced. The key adsorption parameters such as adsorption energy, charge transfer, bond length, bond angle, density of States, charge density difference and electron localization function were calculated and analyzed. The adsorption of SO2, H2 S, SOF2 and CF4 was analyzed by Ni-ZIF-8 cluster and overall structure adsorption model, and competitive adsorption was introduced to verify single gas. The calculation results show that ni-zif-8 has the best selective adsorption of SO2, and the order of adsorption priority is SO2 > H2 S > SOF2 > CF4 . Therefore, it provides a feasible theoretical basis for the design of gas sensor. Highlights: The model of Ni-doped ZIF-8 cluster is established and compared with that of undoped cluster. The adsorption process of SO2, H2 S, SOF2, CF4 on Ni-doped ZIF-8 clusters was simulated. Competitive adsorption can be used to evaluate the correctness of single gas adsorption. Ni-doped cluster model has been proved to be a method to analyze macromolecules.